Pengaruh Beasiswa LPDP terhadap Peningkatan Produktivitas Tenaga Kerja Indonesia di Era Globalisasi - Muhammad Favian Nabil; Alifah Nasrulloh; Yuslimia Jaguar; Rasyad Nu'Man; Salsabila As Zahra; Luthfaira Firyaal Putri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This article discusses the influence of the Education Fund Management Institute (LPDP) scholarship program on increasing the productivity of Indonesian workers in the era of globalization. Through a qualitative descriptive approach and survey, this study analyzes the contribution of LPDP alumni in leadership, social, and economic aspects after completing their studies, both domestically and abroad. The results of the literature study and survey indicate that the LPDP scholarship has a significant impact on increasing the competence, leadership skills, and competitiveness of scholarship recipients in the global job market. This program also plays a role in reducing the level of educated unemployment and strengthening collaborative networks in various sectors. However, there are challenges in implementation, especially related to alumni who are reluctant to return to Indonesia after studying. Therefore, a comprehensive strategy is needed, including strengthening the departure preparation program and post-study monitoring, to ensure the effectiveness and sustainability of the LPDP program's impact on national human resource development.